Experience of dressing changes and wound care for a patient with skin tissue necrosis caused by extravasation of norepinephrine (去甲肾上腺素外渗所致皮肤组织损伤1例的换药护理体会) - LIN Yijuan (林艺娟); WANG Xiaoxia (王小霞) (中西医结合护理)
This paper summarized the experience of dressing changes and wound care for a patient with skin tissue necrosis caused by extravasation of norepinephrine. After assessment of patient’s general conditions and multidisciplinary team consultation, the effective dressing changes and wound care plan using the Tissue, Infection, Moisture, Edge (TIME) framework and Traditional Chinese Medicine external treatment was carried out. Considerable efforts were also made to enhance the basic nursing, nutrition support and psychological care during the hospitalization. (本文总结1例去甲肾上腺素外渗引起右下肢大面积皮肤组织损伤患者的换药护理体会。经全身评估及多学科会诊, 根据伤口管理的TIME原则以及中医外治理论实施有效的换药处理, 同时加强基础护理、营养支持和心理护理。)